Efektifitas Ekstrak Daun Sirih Hijau (Piper Betle) sebagai Insektisida Nabati terhadap Mortalitas Lalat Rumah (Musca domestica) - Rinaldi Daswito; Rima Folentia; M Yusuf M F (Poltekkes Kemenkes Maluku, 2019)
One of the diseases that can be transmitted by flies is diarrhea. Green betel leaf contains essential oils, chavicol, arecoline, phenol, and tannins which function as plant-based insecticides. This study aimed to determine the effectiveness of green betel leaf extract (Piper betel) as a plant-based insecticide on the number of mortality of house flies (Musca domestica). The research was an experimental study used After Only Design used the One Way Anova test with a 95% confidence level. The samples used were 360 ​​house flies. Each treatment of 30 house flies with 4 repetitions and used three concentrations of green betel leaf extract (25%, 50%, 75%). The study was conducted at the Chemistry and Microbiology Laboratory of Health Polytechnic Tanjungpinang, while the location of the fly collection was at the Tokojo Garbage Collection Station in Bintan Regency. The number of mortality of house flies at a concentration of 25% was 81 heads (67.5%), 50% concentrations were 93 heads (77.5%), and at a concentration of 75% were 103 heads (85.83%). There was an effect of green betel leaf extract on the mortality of house flies (p-value 0.0001 <0.05) with the most effective concentration of 75%. Further research is needed to obtain a finished product utilizing green betel leaf extract as a vegetable insecticide, especially in controlling the fly vector. Need further research on the use of green betel leaf extract as a vegetable insecticide controlling the fly vector by taking into account the amount of spraying and the age of the fly. Keywords: Green betel leaf extract , organic insecticide, houseflies